Infrared Spectroscopic Analysis of Chemical Composition of Urolithiasis Among Serving Nepalese Soldiers- An Institutional study - Bhandari, Bharat Bahadur; Basukala, Sunil; Thapa, Narayan; Thapa, Bikash Bikram; Phuyal, Anjit (Medical Journal of Shree Birendra Hospital, 2022)
Introduction: Various pathologic and metabolic diseases might manifest as renal stones. Acquiring knowledge of the urinary stone constituents is important. Kidney stone analysis is recommended in the basic evaluation of stone disease. This study aims to identify the chemical composition of renal stones and briefly identify the predisposing factors. Methods: This was a retrospective analytical study conducted from May 01 2018 to May 30, 2020 for a period of two years in a 750-bedded tertiary care hospital, Shree Birendra Hospital (SBH), Kathmandu, Nepal. All patients who underwent Fourier transform infrared spectroscopy (FT-IR) analysis of the retrieved calculi were included in the study. The type of surgery performed was decided by the operating surgeon based on the treatment options available at the center and the recent evidences on management of the stone. The study was conducted after an approval from institutional Review Board (IRB) of NAIHS. Results: A total 400 patients underwent Infrared spectroscopic analysis (FT-IR) for the retrieved stone. Among them, majority of urolithiasis was seen among male population 277 (69.2%) with an age group between 31 – 45 years {204 (51%)}. Calcium - oxalate was detected in majority of cases 257 (64.25%) followed by struvite 90 (22.5%) and mixed stones 53 (13.2 %). Conclusions: Majority of the patients in our study had kidney stone followed by ureteric stone. The predominance of calcium oxalate stones was seen in kidney stones followed by Struvite and mixed stones.